2014
DOI: 10.1016/j.tim.2014.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic potential of avian influenza A (H7N9) viruses

Abstract: Avian influenza viruses rarely infect humans, but the recently emerged avian H7N9 influenza viruses have caused sporadic infections in humans in China, resulting in 440 confirmed cases with 122 fatalities as of May 16, 2014. In addition, epidemiologic surveys suggest that there have been asymptomatic or mild human infections with H7N9 viruses. These viruses replicate efficiently in mammals, show limited transmissibility in ferrets and guinea pigs, and possess mammalian-adapting amino acid changes that likely c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
79
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(82 citation statements)
references
References 114 publications
1
79
0
Order By: Relevance
“…Pathogenesis of first-, second-, and third-wave H7N9 viruses in ferrets. The presence of amino acid changes among H7N9 viruses indicative of mammalian adaptation warrants the examination of recently isolated H7N9 viruses in multiple mammalian models (33). We first examined the precursor LPAI H7N9 virus shv/Egypt/07 in ferrets, which shares high surface glycoprotein amino acid identity with Anhui/1/13 virus and was previously shown to exhibit reduced virulence in the mouse model compared with human isolates from 2013 (28).…”
Section: H7n9 Virus Information and Genetic Diversitymentioning
confidence: 99%
“…Pathogenesis of first-, second-, and third-wave H7N9 viruses in ferrets. The presence of amino acid changes among H7N9 viruses indicative of mammalian adaptation warrants the examination of recently isolated H7N9 viruses in multiple mammalian models (33). We first examined the precursor LPAI H7N9 virus shv/Egypt/07 in ferrets, which shares high surface glycoprotein amino acid identity with Anhui/1/13 virus and was previously shown to exhibit reduced virulence in the mouse model compared with human isolates from 2013 (28).…”
Section: H7n9 Virus Information and Genetic Diversitymentioning
confidence: 99%
“…We found that memory CD4 T cells specific for H5 HA persisted in subjects vaccinated many years earlier and that these could be recruited into a subsequent immune response to vaccination, enabling a greatly enhanced antibody response to a serologically distinct H5N1-derived virus (20). Should avian influenza viruses continue to pose a threat to humans (54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64), such a prepandemic strategy could enhance vaccine responsiveness in "at risk" subjects and enhance early and potentially protective antibody responses in infected individuals.…”
Section: Discussionmentioning
confidence: 93%
“…They are routinely isolated from wild birds and occasionally from pigs and other mammalian species. Although H9N2 viruses are only endemic in poultry currently, they are the leading candidates with the potential to be transmitted to humans and cause lethal infections (Watanabe et al, 2014).…”
Section: Introductionmentioning
confidence: 99%